Targeting the untargetable KRAS in cancer therapy - Pingyu Liu; Yijun Wang; Xin Li (Elsevier, 2019)
RAS is one of the most well-known proto-oncogenes. Its gain-of-function mutations occur in approximately 30% of all human cancers. As the most frequently mutated RAS isoform, KRAS is intensively studied in the past years. Despite its well-recognized importance in cancer malignancy, continuous efforts in the past three decades failed to develop approved therapies for KRAS mutant cancer. KRAS has thus long been considered to be undruggable. Encouragingly, recent studies have aroused renewed interest in the development of KRAS inhibitors either directly towards mutant KRAS or against the crucial steps required for KRAS activation. This review summarizes the most recent progress in the exploration of KRAS-targeted anticancer strategies and hopefully provides useful insights for the field. KEY WORDS: KRAS, Oncogene, Mutation, Cancer, Inhibitor, Targeted therapy